2016
DOI: 10.1016/j.appet.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Recollections of pressure to eat during childhood, but not picky eating, predict young adult eating behavior

Abstract: Picky eating is a childhood behavior that vexes many parents and is a symptom in the newer diagnosis of Avoidant/Restrictive Food Intake Disorder (ARFID) in adults. Pressure to eat, a parental controlling feeding practice aimed at encouraging a child to eat more, is associated with picky eating and a number of other childhood eating concerns. Low intuitive eating, an insensitivity to internal hunger and satiety cues, is also associated with a number of problem eating behaviors in adulthood. Whether picky eatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…Indeed, in a recent cross-sectional study of college students, perceived parental pressure to eat during childhood was predictive of higher levels of picky eating in young adulthood. 39 Of course, it is unclear whether parental pressure is a cause or consequence of childhood picky eating, and the generalizability to clinical populations is unknown. Berlin and colleagues 40 have argued that the Feeding Dynamics model does not apply to youth on the tails of the body mass index distribution (which may include those with low-weight feeding disorders now classified as ARFID).…”
Section: What Is Currently Known?mentioning
confidence: 99%
“…Indeed, in a recent cross-sectional study of college students, perceived parental pressure to eat during childhood was predictive of higher levels of picky eating in young adulthood. 39 Of course, it is unclear whether parental pressure is a cause or consequence of childhood picky eating, and the generalizability to clinical populations is unknown. Berlin and colleagues 40 have argued that the Feeding Dynamics model does not apply to youth on the tails of the body mass index distribution (which may include those with low-weight feeding disorders now classified as ARFID).…”
Section: What Is Currently Known?mentioning
confidence: 99%
“…These hypotheses are supported by evidence that critical comments and teasing about eating, weight, and appearance are risk factors for disordered eating (e.g., Fairweather‐Schmidt & Wade, ; Menzel et al, ) and that pressures from parents, peers and the media on losing weight predict the use of extreme weight loss strategies over time (McCabe & Ricciardelli, ). Likewise, parental coercive control over eating has been associated with the development of disordered eating over time (e.g., Ellis, Galloway, Webb, Martz, & Farrow, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between pressure to eat and weight in children is thought to be bidirectional and dependent on context. Some researchers have suggested that parents may respond to lower child weight by pressuring the child to eat, which then has the counterproductive effect of disrupting self-regulation and intuitive eating over time ( 25 ). However, some types of pressure to eat have been shown to predict higher food intake, higher weight status, or greater eating in the absence of hunger ( 24 , 29 – 31 ), possibly because parents react to perceived lower weight by pressuring the intake of energy-dense foods ( 24 ).…”
Section: Introductionmentioning
confidence: 99%